Strategi Pembelajaran Guru PAI dalam Mengatasi Kesulitan Kegiatan Belajar Mengajar pada Era Pandemi Covid-19 - Sari Sartika Lubis; Siti Istiqomah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
This research aims to determine the application of learning strategies carried out by schools, especially PAI teachers in overcoming the difficulties of teaching and learning activities in grade 4 SD Dua Mei Ciputat. The method used in this research is qualitative with qualitative descriptive research. Data collection techniques using interviews, observation and documentation. Primary data sources come from school principals, PAI teachers, and 4th grade students, while secondary data sources come from school data, books, journals, articles and theses. The data analysis technique uses a data reduction model, data presentation, and data verification or conclusions. The results of this study indicate that the implementation of contextual learning strategies has been going well. This is seen from several aspects, namely PAI teachers have planned learning strategies in the era of the covid-19 pandemic, minimized difficulties in online teaching and learning activities and collaborated in online teaching and learning activities with parents. The supporting factors in carrying out online learning include learning strategy innovations, assistance with school wifi facilities for teachers and good coordination between parents and teachers. While the inhibiting factors are the internet network which is less stable, there are some parents who do not understand the use of the internet and the competence of students decreases